2013
DOI: 10.1590/s0100-204x2013000400011
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho de cordeiros confinados, alimentados com dietas à base de torta de girassol

Abstract: Resumo -O objetivo deste trabalho foi avaliar os efeitos da inclusão da torta de girassol na dieta de cordeiros em confinamento sobre o desempenho produtivo dos animais. Utilizaram-se 40 cordeiros sem raça definida, não castrados, com peso médio inicial de 20,17±2,66 kg, alimentados com 0, 7, 14, 21 e 28% de torta de girassol na dieta (base seca). O experimento foi conduzido em delineamento de blocos ao acaso. A inclusão de torta de girassol na dieta não alterou o consumo médio de matéria seca (883,58 g por di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…The late development of the Longissimus lumborum muscle can also explain the reduction of its yield. Similar results were observed by Rodrigues et al (2013) when evaluating increasing levels of sunflower cake (0, 7, 14, 21 and 28%) in sheep's diets; the yields decreased as the cake levels increased.…”
Section: Resultssupporting
confidence: 80%
“…The late development of the Longissimus lumborum muscle can also explain the reduction of its yield. Similar results were observed by Rodrigues et al (2013) when evaluating increasing levels of sunflower cake (0, 7, 14, 21 and 28%) in sheep's diets; the yields decreased as the cake levels increased.…”
Section: Resultssupporting
confidence: 80%
“…Biodiesel production generates many by-products (cakes and refusals) available for feeding ruminants [ 8 , 9 ]. One example, sunflower cake, is obtained after the mechanical extraction of sunflower ( Helianthus annuus ) oil [ 10 ], has high concentrations of lipids (160 g/kg on a DM basis) and proteins (249 g/kg on a DM basis) [ 11 ], and has been recommended for total or partial replacement of the soybean meal and corn components [ 11 , 12 ] in feed for goats [ 13 ], lambs [ 14 ] and steers [ 3 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the addition of CP to the low-quality forage offered to ruminant animals can reduce feeding expenses while maintaining or enhancing animal performance and the intake and digestibility of nutrients [6,7]. To improve the productivity of livestock grazing on low-quality forages, protein supplements such as soybean meal (SBM) are used in Jordan and worldwide [8]. Ramos et al [9] reported that the growth performance was improved in lambs receiving supplemental graded levels of protein (i.e., 12%, 16%, or 20% CP) compared with lambs not fed supplemental protein when grazing low-quality forages.…”
Section: Introductionmentioning
confidence: 99%